2015
DOI: 10.1158/1535-7163.mct-15-0374
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expression of Key DNA Damage Repair Genes after Epigenetic-Induced BRCAness Dictate Synthetic Lethality with PARP1 Inhibition

Abstract: The triple-negative breast cancer (TNBC) subtype represents a cancer that is highly aggressive with poor patient outcome. Current preclinical success has been gained through synthetic lethality, targeting genome instability with PARP inhibition in breast cancer cells that harbor silencing of the homologous recombination (HR) pathway. Histone deacetylase inhibitors (HDACi) are a class of drugs that mediate epigenetic changes in expression of HR pathway genes. Here, we compare the activity of the pan-HDAC inhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Notch signaling controls cell processes, including cancer cell and cancer stem cell fate determination. NOTCH2 expression is specifically downregulated in CCC (66). Notch signaling and ERBB2 appear to be mutually exclusive, demonstrating that Notch signaling is also a potential synthetic lethal partner of ERBB2 (67).…”
Section: Discussionmentioning
confidence: 95%
“…Notch signaling controls cell processes, including cancer cell and cancer stem cell fate determination. NOTCH2 expression is specifically downregulated in CCC (66). Notch signaling and ERBB2 appear to be mutually exclusive, demonstrating that Notch signaling is also a potential synthetic lethal partner of ERBB2 (67).…”
Section: Discussionmentioning
confidence: 95%
“…We showed correlation of RAD51 expression and IC 50 in these cell lines. In contrast, high RAD51 expressing HCC1937 increases NHEJ activity when RAD51 is inhibited 19 . We observed a slightly higher IC 50 in this cell line.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 91%
“…Varying spacer length in compound 17, with one methylene unit shorter (15) or longer (16), did not improve activity and indicated optimal positioning of the aromatic ring in 17. Of the substituted benzyl series, fluoro (18)(19)(20), nitro (21-22) and p-hydroxy (23) analogues showed comparable activity. A polar substrate, such as pacetamidomethyl (24) and carboxylic acid (25-26), were detrimental, while 3,4-dichloro (27) conferred a slight improvement.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner to PARP1 inhibitors, the suppression of RAD52 reduces homologous recombination and results in synthetic lethality in cells deficient in BRCA1/2 or associated proteins (including partner and localizer of BRCA2, RAD51B/C/D and XRCC2/3), whilst sparing normal cells (44). RAD51/RAD54B and PARP1 have been reported to function as synthetic lethal interactors, where it was thus revealed that PARP1 may be a novel candidate drug target in RAD51/RAD54B-deficient cells (45). Chromatin remodeling proteins are often contained within multiprotein complexes (43).…”
Section: Category 3: Subunit Components That Form Heteromeric Complexesmentioning
confidence: 99%